1993
DOI: 10.1002/j.1460-2075.1993.tb06064.x
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of chromosomal protein HMG-17 during replication affects the nucleosomal ladder and transcriptional potential of nascent chromatin.

Abstract: A cell‐free system from Xenopus eggs was used to study the role of chromosomal protein HMG‐17 in the generation of the chromatin structure of transcriptionally active genes. Addition of HMG‐17 protein to the extracts, which do not contain structural homologs of the HMG‐14/−17 protein family, indicates the protein is incorporated into the nascent template during replication, prior to completion of chromatin assembly. The protein binds to and stabilizes the structure of the nucleosomal core thereby improving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
5
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 62 publications
7
69
5
1
Order By: Relevance
“…2E). This experiment revealed that there was no apparent depletion of H2A-H2B upon incorporation of HMG17 into the chromatin, which is consistent with the results of previous studies in which the protein composition of HMG 17-containing chromatin was examined (see, e.g., Albright et al 1980;Shick et al 1985;Crippa et al 1993).…”
Section: Hmgi 7 Is Efficiently Incorporated Into Chromatin During Asssupporting
confidence: 90%
See 4 more Smart Citations
“…2E). This experiment revealed that there was no apparent depletion of H2A-H2B upon incorporation of HMG17 into the chromatin, which is consistent with the results of previous studies in which the protein composition of HMG 17-containing chromatin was examined (see, e.g., Albright et al 1980;Shick et al 1985;Crippa et al 1993).…”
Section: Hmgi 7 Is Efficiently Incorporated Into Chromatin During Asssupporting
confidence: 90%
“…Hence, these results indicate that the stimulation of GAL4-VP 16-activated transcription by HMG 17 is chromatin-dependent, which suggests that the specific binding of HMG17 to nucleosomal DNA, as characterized previously ( Fig. 2D; Albright et al 1980;Mardian et al 1980;Sandeen et al 1980;Crippa et al 1992Crippa et al , 1993A1-HMG17 is a t r a n s c r i p t i o n a l c o a c t i v a t o Binding of GAL4{1-147)to the template is not sufficient for transcriptional potentiation by HMG17. GAL4(1-147)contains the amino-terminal 147 amino acid residues of the yeast GAL4 protein and is identical to GAL4-VP16, except that it does not contain the transcriptional activation domain derived from the herpesvims VP16 protein.…”
Section: Bottom (A)hmg17supporting
confidence: 84%
See 3 more Smart Citations